جريمة افشاء اسرار الدفاع عن البلاد - حسين الاء ناصر; حسين احمد عبد الامير (Journal of Legal Sciences, 2019)
Maintaining and concealing secrets of defending country are important duties on the shoulder of community. They are important because these secrets can be considered significant state secrets which linked to the state existence and survival and on which the state security depends. Some professions have many significant secrets exposed for any one in charge of a public service or any officer because of his daily job, otherwise it was impossible to see such secrets or know about them.